GE_GERICHTE P/1185/2017 vom 31. Mai 2018 - GE Cour de justice (2018)
JUGEMENT PAR DÉFAUT ; VIOLATION DES RÈGLES DE LA CIRCULATION | LCR.90.al1; LCR.27.al1; CPP.368.al1; CPP.399.al3; CPP.110.al1; CPP.371.al1